Role of bundled intervention in reducing surgical site infection rate in gynecologic surgeries - Singh, Nisha; Rai, Shweta; Agrawal, Shuchi; Banerjee, Gopa; Singh, Renu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Surgical site infection (SSI) is most common nosocomial infection (15%) among surgical patient’s and contributes significantly to morbidity and mortality. CDC (2015) provides “bundled intervention for prevention of SSI. The present study was planned to evaluate the feasibility and usefulness of these bundled intervention in reducing SSI in our setup. Objectives of this study to study the effect of bundled interventions on SSI in gynaecologic surgery. Methods: A total 50 cases undergoing gynecological surgery in elective OT included in pilot group and bundled intervention followed these pilot group cases compared with 50 control group operated in same OT in which bundled intervention not followed outcome measures recorded were Incidence of SSI, type of SSI, need for antibiotic usage, need for secondary suturing, duration of hospital stay. Results: Out of 50 subjects in pilot group, five developed signs and symptoms of SSI giving an SSI rate of 10%. Out of those five, two had superficial SSI and three had deep SSI, none of the patient had organ space SSI.SSI rate in 50 cases operated in the same operating room during the same time period without use of bundled interventions (control group) was 12%. Conclusions: Bundled approach is easy and feasible in all setups. It adds only three extra minutes to the total duration of the surgery with risk reduction of SSI.